2010
DOI: 10.1143/jjap.49.095202
|View full text |Cite
|
Sign up to set email alerts
|

Finite-Difference Time-Domain Analysis of Scanning Tunneling Microscope Light Emission Spectra

Abstract: A theory describing multiphonon resonant Raman scattering (MPRRS) processes in wide-gap diluted magnetic semiconductors is presented, with Cd 1−x Mn x Te as an example. The incident radiation frequency ω l is taken above the fundamental absorption region. The photoexcited electron and hole make real transitions through the LO phonon, when one considers Fröhlich (F) and deformation potential (DP) interactions. The strong exchange interaction, typical of these materials, leads to a large spin splitting of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Although this method allows us to reproduce various types of experimental STM-LE results, it is only applicable to the system consisting of simple layered structures. In contrast, the FDTD method has been recently applied to the spectral analysis of the STM-LE. , One of the advantages of the FDTD is that the electromagnetic calculations can be performed for the sample with the arbitrary shapes. Recently, it was confirmed that the FDTD calculation provides predictions which are consistent with those of the calculation based on the dielectric theory .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although this method allows us to reproduce various types of experimental STM-LE results, it is only applicable to the system consisting of simple layered structures. In contrast, the FDTD method has been recently applied to the spectral analysis of the STM-LE. , One of the advantages of the FDTD is that the electromagnetic calculations can be performed for the sample with the arbitrary shapes. Recently, it was confirmed that the FDTD calculation provides predictions which are consistent with those of the calculation based on the dielectric theory .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the FDTD method has been recently applied to the spectral analysis of the STM-LE. , One of the advantages of the FDTD is that the electromagnetic calculations can be performed for the sample with the arbitrary shapes. Recently, it was confirmed that the FDTD calculation provides predictions which are consistent with those of the calculation based on the dielectric theory . Since the present study deals with the optical responses of nanoparticles, we employed the FDTD method to calculate the STM-LE spectra.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations